Characteristics of Foamed Gel for Coal Spontaneous Combustion Prevention and Control. Issue 6 (3rd June 2017) - Zhang, Leilin; Shi, Biming; Qin, Botao; Wu, Qing; Dao, Vanchi
ABSTRACT: Foamed gel, a new technology for preventing and controlling coal mine fires, was put forward and developed in order to overcome the deficiency of fire-fighting technologies and materials in coal mines. The properties of adhesiveness, permeability, cementation, and plugging of foamed gel have been experimentally studied. It can be shown from the results that the apparent viscosity of foamed gel reaches 7274 mPa·s, 18 times that of the stock solution. The permeability of foamed gel is 33.84%, 2.35 and 1.65 times of that of water and common foam, respectively. Furthermore, the time of permeability reaching the maximum is only 40 min, half of that of water and common foam. One day later, the weight of slack coal coagulated by foamed gel is 57–93.8% of that of the coal sample, and it is still 13.4–52.6% of that after 10 days. The foamed gel cannot only fill the fractures among coal and block air leakage, but also endure the wind pressure of over 2500 Pa. Thus, it can effectively prevent and control coal spontaneous combustion. Furthermore, by using spontaneous combustion testing apparatus, the researches have been conducted to investigate the release rate of CO of coal mixed with the foamed gel. It can be seen from the results that the inhibiting effect of foamed gel is significant, which can efficiently slow down the oxidation rate of coal and control the release amount of CO.